2017
DOI: 10.3906/sag-1603-22
|View full text |Cite
|
Sign up to set email alerts
|

Role of hygienic factors in the etiology of allergic disorders in children

Abstract: Background/aim: We investigated the role of body flora and chronic inflammatory infections in the etiology of allergic disorders in Turkish children. Materials and methods:Forty pediatric asthma patients with positive skin prick tests and 40 age-matched healthy subjects with negative skin prick tests were enrolled in this cross-sectional study. Serum H. pylori IgG, viral hepatitis serology, IL-10, and TGF-beta levels were measured. Stool and throat cultures were taken and tested for occurrence of microorganism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 19 publications
1
3
0
3
Order By: Relevance
“…This supports data from a smaller case‐control study showing a nonsignificant lower H. pylori positivity among children with allergies compared with individuals without allergies: 13.9% (17/122) vs 22.4% (22/98), respectively . In contrast, 2 other case‐control studies showed a significantly lower seroprevalence of H. pylori among allergic children compared with individuals without allergies: 25.6% (23/90) vs 44.4% (40/90) and 20% (36/180) vs 60% (108/180), respectively . In addition, the latter study also demonstrated significantly higher serum IL‐10 levels in nonatopic subjects …”
Section: Clinical Manifestationssupporting
confidence: 85%
See 3 more Smart Citations
“…This supports data from a smaller case‐control study showing a nonsignificant lower H. pylori positivity among children with allergies compared with individuals without allergies: 13.9% (17/122) vs 22.4% (22/98), respectively . In contrast, 2 other case‐control studies showed a significantly lower seroprevalence of H. pylori among allergic children compared with individuals without allergies: 25.6% (23/90) vs 44.4% (40/90) and 20% (36/180) vs 60% (108/180), respectively . In addition, the latter study also demonstrated significantly higher serum IL‐10 levels in nonatopic subjects …”
Section: Clinical Manifestationssupporting
confidence: 85%
“…In contrast, 2 other case‐control studies showed a significantly lower seroprevalence of H. pylori among allergic children compared with individuals without allergies: 25.6% (23/90) vs 44.4% (40/90) and 20% (36/180) vs 60% (108/180), respectively . In addition, the latter study also demonstrated significantly higher serum IL‐10 levels in nonatopic subjects …”
Section: Clinical Manifestationsmentioning
confidence: 60%
See 2 more Smart Citations
“…Daha sonra yapılan çalışmalarda hijyen hipotezinin biyolojik temelleri desteklenmiş; çocukluk çağı enfeksiyonlarının T helper (Th) 1 yanıtı artırdığı ve atopi gelişiminde önemli olan Th2 yanıtı baskıladığı gösterilmiştir (7)(8)(9)(10)(11). Hipotezin ilk ortaya atıldığı andan itibaren virüs (9,10,(12)(13)(14)(15)(16), bakteri (2,7,9,10,13,17) ya da parazit (3,(8)(9)(10)(11)13) olmak üzere çeşitli çocukluk çağı enfeksiyonları ile atopi arasındaki ilişki araştırılmış; lehte ve aleyhte birçok sonuçla tartışmaya günümüzde de devam edilmiştir (2,(17)(18)(19)(20)(21).…”
unclassified